Managing thymic enlargement in Graves’ disease - C Kamath; J Witczak; M A Adlan; L D Premawardhana (Endocrinology, Diabetes & Metabolism Case Reports, 2019)
Thymic enlargement (TE) in Graves’ disease (GD) is often diagnosed incidentally when chest imaging is done for unrelated reasons. This is becoming more common as the frequency of chest imaging increases. There are currently no clear guidelines for managing TE in GD. Subject 1 is a 36-year-old female who presented with weight loss, increased thirst and passage of urine and postural symptoms. Investigations confirmed GD, non-PTH-dependent hypercalcaemia and Addison’s disease (AD). CT scans to exclude underlying malignancy showed TE but normal viscera. A diagnosis of hypercalcaemia due to GD and AD was made. Subject 2, a 52-year-old female, was investigated for recurrent chest infections, haemoptysis and weight loss. CT thorax to exclude chest malignancy, showed TE. Planned thoracotomy was postponed when investigations confirmed GD. Subject 3 is a 47-year-old female who presented with breathlessness, chest pain and shakiness. Investigations confirmed T3 toxicosis due to GD. A CT pulmonary angiogram to exclude pulmonary embolism showed TE. The CT appearances in all three subjects were consistent with benign TE. These subjects were given appropriate endocrine treatment only (without biopsy or thymectomy) as CT appearances showed the following appearances of benign TE – arrowhead shape, straight regular margins, absence of calcification and cyst formation and radiodensity equal to surrounding muscle. Furthermore, interval scans confirmed thymic regression of over 60% in 6 months after endocrine control. In subjects with CT appearances consistent with benign TE, a conservative policy with interval CT scans at 6 months after endocrine control will prevent inappropriate surgical intervention.